Elevated Prevalence of Viral and Bacterial Infections Among Voluntary Blood Donors in Sleman, Indonesia - Hartalina Mufidah; Handriani Kristanti; Gunawan Gunawan (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Transfusion-transmissible infections (TTIs), such as hepatitis B virus (HBV), hepatitis C virus (HCV), HIV, and syphilis, continue to pose significant challenges to blood safety, particularly in low- and middle-income countries. This study aimed to determine the prevalence and donor-related factors associated with transfusion-transmissible infections (TTIs) in this donor population. This retrospective cross-sectional study utilized secondary data from 656 blood donors screened between 2018 and 2020 at the Indonesian Red Cross, Sleman Regency, Yogyakarta. Donor demographic characteristics and screening outcomes for HBsAg, HCV, HIV, and syphilis were analyzed using binary logistic regression. Statistical significance was determined at a p-value of less than 0.05 with a 95% confidence interval. The overall TTI prevalence were 50.3% for HBsAg, 12.2% for HCV, 22.7% for HIV, and 14.6% for syphilis. Donors aged 46–55 years exhibited 2.2 times higher odds of syphilis positivity than those aged 17–25 years, a statistically significant association (95% CI: 1.013–4.880). Similarly, donors aged 56–65 years had 3.5 times greater odds compared with the same reference group, also showing a statistically significant relationship (95% CI: 1.284–9.363). First-time blood donors showed significantly greater odds of testing positive for syphilis compared with repeat donors (COR = 2.3, 95% CI: 1.457–3.541). These results indicate a considerable burden of TTIs, underscoring the importance of enhancing donor screening systems, incorporating behavioral risk evaluations, and developing region-specific policies, particularly in Sleman.